The Great I-QALY Disaster - Paul Langley (University of Minnesota Libraries Publishing, 2020)
The QALY is an impossible construct; it defies common sense. It fails completely once we consider the axioms of fundamental measurement. Utilities as ordinal scales cannot be used to create QALYS. The QALY should never have been introduced to support the value assessment of pharmaceutical products and devices. The result is 30 years of QALY based assessments of pharmaceutical products and devices which are conceptually and technically wrong. They are a charade and will have contributed mistakenly to thousands of formulary decisions. In the search for a common metric to evaluate cost-effectiveness the impossibility of a QALY was overlooked. The result is a disaster, unfolding over decades. Our next steps must be to abandon the QALY paradigm and look ahead to a new value assessment framework.   Commentary